2016
DOI: 10.1002/bdra.23486
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trend of neural tube defects in five counties in Shanxi province of Northern China, 2000 to 2014

Abstract: The prevalence of NTDs remains high despite a substantial and continuous decrease over the past 15 years. To further reduce NTD risk in the population, fortification staples with folic acid should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 22 publications
6
73
1
Order By: Relevance
“…The subjects were recruited from five rural counties (Xiyang, Shouyang, Taigu, Pingding, and Zezhou) of Shanxi Province in northern China, utilizing a population-based birth defect surveillance program, which has been previously described elsewhere [30]. Birthing hospitals report to the system newborns with major external structural birth defects or fetuses that are terminated due to prenatal diagnosis of such defects.…”
Section: Methodsmentioning
confidence: 99%
“…The subjects were recruited from five rural counties (Xiyang, Shouyang, Taigu, Pingding, and Zezhou) of Shanxi Province in northern China, utilizing a population-based birth defect surveillance program, which has been previously described elsewhere [30]. Birthing hospitals report to the system newborns with major external structural birth defects or fetuses that are terminated due to prenatal diagnosis of such defects.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, from 2003 to 2009, the prevalence was 0.3 per 10,000 live births in Beijing [9]. Although a recent study conducted by Liu and colleagues [10] showed that the prevalence of NTDs presented a continuous decreasing trend and was 31.5 per 10,000 live births in 2014 in the Shanxi Province of China. However, data reflecting the status of NTDs in China during the last decade have been quite limited for other areas.…”
Section: Introductionmentioning
confidence: 99%
“…The whole continent consists of 48 countries, as shown in Table 1 . The dropping prevalence of live-born MMC was also 164 observed in the recently published cohort from China [9] . This trend was attributed to a wider adoption of periconceptional supplementation of folic acid, earlier antenatal diagnosis, and termination of affected pregnancies [10] .…”
Section: Actual Impact Of MMC In Asiamentioning
confidence: 56%
“…This trend was attributed to a wider adoption of periconceptional supplementation of folic acid, earlier antenatal diagnosis, and termination of affected pregnancies [10] . Most of the spina bifida cases are now from the rural area [9] . Asia is more diverse than North America or Europe, since it includes some of the world's least developed as well as highly developed countries.…”
Section: Actual Impact Of MMC In Asiamentioning
confidence: 99%
See 1 more Smart Citation